2008
DOI: 10.1162/jocn.2008.20130
|View full text |Cite
|
Sign up to set email alerts
|

Aging Does Not Affect Brain Patterns of Repetition Effects Associated with Perceptual Priming of Novel Objects

Abstract: This study examined how aging affects the spatial patterns of repetition effects associated with perceptual priming of unfamiliar visual objects. Healthy young (N=14) and elderly adults (N=13) viewed four repetitions of structurally possible and impossible figures while being scanned with BOLD fMRI. Although explicit recognition memory for the figures was reduced in the elder subjects, repetition priming did not differ across the two age groups. Using multivariate linear modeling, we found that the spatial net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 55 publications
5
38
2
Order By: Relevance
“…The current findings diverge from fMRI findings showing greater neural activity for repetition of unfamiliar faces, meaningless symbols, and pseudowords, whereas repetition of familiar stimuli produces less activity (Henson et al, 2000;Fiebach et al, 2005;Soldan et al, 2008). James and Gauthier (2006) argued that the priming literature, showing reduced activity sometimes and enhanced activity other times, can best be explained by an accumulation model that describes the temporal dynamics of neural activity.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The current findings diverge from fMRI findings showing greater neural activity for repetition of unfamiliar faces, meaningless symbols, and pseudowords, whereas repetition of familiar stimuli produces less activity (Henson et al, 2000;Fiebach et al, 2005;Soldan et al, 2008). James and Gauthier (2006) argued that the priming literature, showing reduced activity sometimes and enhanced activity other times, can best be explained by an accumulation model that describes the temporal dynamics of neural activity.…”
Section: Discussioncontrasting
confidence: 95%
“…Observing negative repetition effects (both negative ERP old/new effects and fMRI deactivations) may require negligible explicit memory. Explicit retrieval was not strongly discouraged in previous studies that found positive repetition effects with unfamiliar stimuli (Henson et al, 2000;Fiebach et al, 2005;Soldan et al, 2008). Indeed, the first neuroimaging study to identify increased ventral visual activity for priming of unfamiliar objects also showed highly accurate explicit recognition in the same circumstances, with concomitant hippocampal activation for both priming and recognition attributed to explicit retrieval (Schacter et al, 1995).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…however, each process has separate mechanisms 26,30,31 . Priming is influenced by frontal cortex, which may reflect its attentional demands [32][33][34] and procedural memory is influenced by the striatum, sensorimotor cortex and cerebellum 30,35,36 , which may reproduce its motor skills. explicit memory impairment is one of the earliest AD symptoms, and its loss characterizes all the stages of AD 37 .…”
Section: Explicit Memory Deficits Affect the Implicit Memory?mentioning
confidence: 99%
“…For instance, Henson et al (2000) has shown that the repetition of truly unfamiliar visual stimuli, such as unfamiliar faces and symbols, could lead to an increase in neural activity in the right fusiform region measured as an fMRI signal, while repeated exposure to familiar stimuli elicits decaying activity. Similarly, Soldan, Gazes, Hilton, and Stern (2008) have registered repetition enhancement in the occipital-temporal cortex related to the repetition of unfamiliar stimuli and decreases in neural activity for familiar stimuli. A study by Fiebach, Gruber, and Supp (2005) presented similar EEG results showing dissociable trends for the repetition of familiar words versus unfamiliar pseudowords.…”
Section: Dissociable Forms Of Repetition Primingmentioning
confidence: 82%